Immediate versus staged revascularisation in multivessel coronary disease: an updated meta-analysis. (25th November 2020) - Von Renteln, F; Hassan, S; Szummer, K; Edfors, R; Venetsanos, D; Kober, L; Braunschweig, F; Lewinter, C
Abstract: Background: Percutaneous coronary interventions (PCIs) are often aimed at the culprit vessel in acute coronary syndromes (ACSs) followed by revascularisation of other stenoses later in the index hospitalisation or shortly after discharge. PCI delay of non-culprit coronary vessels stenoses is supported by lower contrast fluid use and thrombocyte aggregation. Distinct coronary interventions increase the risk of both non- and coronary artery complications, e.g. acute abdominal and periphery artery bleeding, suggesting undertaking all PCIs at the same time. Purpose: To assess the effect on mortality and re-myocardial infarction (MI) of immediate versus staged revascularisation in multivessel coronary disease, with the latter constrained to initial PCI of the culprit coronary vessel. Methods: The syntax of "randomised controlled trial (RCT) & acute coronary syndrome & complete revascularisation" was undertaken in PubMed. Clinical characteristics were gathered at the index hospitalisation. The intervention scenario was acute coronary syndrome or not. Meta-analyses calculated relative risk (RR) reductions on outcomes of 1) mortality and 2) re-MI. Meta-regression assessed linear difference between interventional treatment benefits and baseline characteristics. Results: A total of 148 studies was found. Of those, 8 was found eligible for further analyses and their baseline characteristics are shown in Table 1. Comparison of immediate versus staged revascularisation on mortality was nonsignificant (RR, 1.19; 95% CI: 0.78–1.81, p=0.43) (Figure 1). The impact of Immediate vs staged revascularisation on re-MI was also nonsignificant (RR, 0.83; 95% CI: 0.44–1.55, p=0.56). Meta-regression found no associations between the outcomes and study characteristics (not shown). Conclusion: The intervention of immediate compared to staged revascularisation assessed on outcomes of all-cause mortality and re-MI were nonsignificant. Funding Acknowledgement: Type of funding source: None